The Role of Project-Based Learning and Mobile Learning in Fostering Student Engagement in TVET - Sardi, Juli; Darmansyah; Oriza Candra; Devi Faizah Yuliana; Habibullah (Journal of Technical Education and Training, 2025)
This study examines the role of integrating Project-Based Learning (PjBL) and Mobile Learning (ML) in enhancing Student Engagement (SE) in TVET. Using a quantitative method with an explanatory causal design, this research explores direct and indirect relationships among PjBL, ML, and SE through Structural Equation Modeling (SEM). Data were collected from 40 vocational education students enrolled in an Electrical Motor Installation course. The findings reveal that PjBL significantly enhances SE through constructive, independent, collaborative, and contextual learning. Meanwhile, ML amplifies these benefits by providing flexibility, accessibility, and interactive platforms, effectively mediating the impact of PjBL on SE. Together, these approaches address engagement’s cognitive, behavioral, and emotional dimensions, creating a synergistic framework that aligns educational practices with the demands of a technology-driven workforce. The study underscores the importance of integrating PjBL and ML to foster autonomy, real-world relevance, and adaptability in TVET students. The practical implications of this would require educators to use the approaches to design dynamic learning experiences, institutions to invest in the necessary technological infrastructure and training of educators, and policymakers to support such innovations with targeted policies and resources.